Food selection by bacterivorous protists: insight from the analysis of the food vacuole content by means of fluorescence in situ hybridization - Jezbera, Jan; Hornák, Karel; Simek, Karel (FEMS microbiology ecology, 2005)
A modified fluorescence in situ hybridization (FISH) method was used to analyze bacterial prey composition in protistan food vacuoles in both laboratory and natural populations. Under laboratory conditions, we exposed two bacterial strains (affiliated with beta- and gamma-Proteobacteria -- Aeromonas hydrophila and Pseudomonas fluorescens, respectively) to grazing by three protists: the flagellates Bodo saltans and Goniomonas sp., and the ciliate Cyclidium glaucoma. Both flagellate species preferably ingested A. hydrophila over P. fluorescens, while C. glaucoma showed no clear preferences. Differences were found in the digestion of bacterial prey with B. saltans digesting significantly faster P. fluorescens compared to two other protists. The field study was conducted in a reservoir as part of a larger experiment. We monitored changes in the bacterial prey composition available compared to the bacteria ingested in flagellate food vacuoles. Bacteria detected by probe HGC69a (Actinobacteria) and R-BT065 were negatively selected by flagellates. Bacteria detected by probe CF319a were initially positively selected but along with a temporal shift in bacterial cell size, this trend changed to negative selection during the experiment. Overall, our analysis of protistan food vacuole content indicated marked effects of flagellate prey selectivity on bacterioplankton community composition.
Keywords: predátorské chování; stravovací zvyklosti; hybridizace in situ fluorescenční; RNA, Ribosomal, 16S; řeky; Eukaryota; ribozomální DNA; vakuoly; Aeromonas hydrophila; Rivers; Vacuoles; Pseudomonas fluorescens; Predatory Behavior; DNA, Bacterial; DNA bakterií; Animals; Ciliophora; zvířata; RNA ribozomální 16S; In Situ Hybridization, Fluorescence; DNA, Ribosomal; Feeding Behavior